UPAYA PENINGKATAN RASA PERCAYA DIRI PADA ANAK USIA 2-4 TAHUN MELALUI MEDIA BONEKA JARI DI KB QUR’ANI ‘AISYIYAH II KOTA PROBOLINGGO - Fitriatul Aini; Agustiarini Eka Dheasari (incrementapedia, 2022)
This study aims to determine the effect of using finger puppet media on children's self-confidence, and how the results of applying finger puppet media can increase children's self-confidence. The research results in the first cycle increased by 70.3%, and in the second cycle it increased again by 88.9%. From observations made by researchers, it is evident that finger puppet media can increase children's self-confidence. This type of research is classroom action research. Confidence is a measure of how much courage a person has to appear in public, answer questions, and have fun together in activities. Finger puppets are a type of learning media that are played using fingers. Based on preliminary observations conducted by researchers on KB Qur'ani 'Aisyiyah II children, it was found that 60% of them had low self-esteem problems. Data collection techniques used in this study are observation, interviews, and documentation.